2015
DOI: 10.1140/epjd/e2015-60200-y
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact fragmentation of adenine: partial ionization cross sections for positive fragments

Abstract: Abstract. Using computer-controlled data acquisition we have measured mass spectra of positive ions for electron impact on adenine, with electron energies up to 100 eV. Ion yield curves for 50 ions have been obtained and normalized by comparing their sum to the average of calculated total ionization cross sections. Appearance energies have been determined for 37 ions; for 20 ions for the first time. All appearance energies are consistent with the fragmentation pathways identified in the literature. Second onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 39 publications
4
36
0
3
Order By: Relevance
“…In this ion Fig 5a). No peak at m/z 84 has been observed from isolated, clustered, or protonated adenine [22,37,39,40], or from protonated uracil [41]. The fact that the U + signals were the same (to within the uncertainty limits) in plots a and c as well as in plots b and d suggests that this result was not simply due to different populations of isolated uracil molecules in the neutral beams.…”
Section: Fig 5 Compares Mpi and Eii Measurements Carried Out On Uracmentioning
confidence: 82%
“…In this ion Fig 5a). No peak at m/z 84 has been observed from isolated, clustered, or protonated adenine [22,37,39,40], or from protonated uracil [41]. The fact that the U + signals were the same (to within the uncertainty limits) in plots a and c as well as in plots b and d suggests that this result was not simply due to different populations of isolated uracil molecules in the neutral beams.…”
Section: Fig 5 Compares Mpi and Eii Measurements Carried Out On Uracmentioning
confidence: 82%
“…On the experimental side, Burgt et al measured the relative cross sections up to 100 eV and normalized them to absolute values using the average value of various theoretical results at 70 eV. [20][21][22] So far, there exists only one set of absolute cross section measurements. [23][24][25][26] These measurements, carried out up to 200 eV of impact energies, vary from theory by a factor of 0.5-2 depending on the molecule.…”
mentioning
confidence: 99%
“…3 shows experimentally determined total ionization cross sections from threshold to 500 eV. The available theoretical [13][14][15][16][17][18][19] and measured [20][21][22][23][24][25][26] cross sections are also shown in the figure. The measurements [23][24][25][26] used a crossed beam method and the absolute cross sections were obtained directly by measuring the total ion current, the target beam density, and the volume overlap between the beams using the geometrical details of the setup.…”
mentioning
confidence: 99%
“…Kumar et al [36] compare and discuss experimental studies of DNA irradiated with electrons. Theoretical studies of electron attachment are reported in by Lacombe et al [37] van der Burgt et al [38] experimentally studied electron impact fragmentation of adenine. A study of dissociative electron attachment to sulfur containing compounds is presented by Kopyra and W ladziński [39].…”
Section: Introductionmentioning
confidence: 99%